Rancang Bangun Prototipe Jemuran Pakaian Otomatis Menggunakan Sensor LDR dan Sensor Hujan Berbasis Mikrokontroler Atmega 328 - Arba'i Yusuf; Iramawati, Isnaeni; Asni Tafrikhatin (Politeknik Piksi Ganesha Indonesia, 2022)
The inter-monsoon season is the transitional period between the rainy season and the summer season. When drying clothes outdoors, it can be quite inconvenient if it suddenly rains, especially during the inter-monsoon season, resulting in clothes not drying optimally. This research aims to assist users in addressing this issue by creating a prototype of an automatic clothes drying rack using an LDR sensor and a rain sensor. The research method employed in this study is the Research and Development approach. The automatic clothes drying rack prototype utilizes an LDR sensor and an DSK MH-RD rain sensor to detect light intensity and rainfall, an Arduino as the microcontroller, and a stepper motor as the mechanism to move the drying rack. If the LDR sensor detects light and the rain sensor does not detect rain, the stepper motor will automatically activate and move the clothes outside. Conversely, if the rain sensor detects the presence of water or the LDR does not detect light, the stepper motor will move the clothes inside. It is hoped that this product can assist users in achieving optimal clothes drying.